Identification of University Resources in an Effort to Design a Disaster Resilience Training Module - Hery Sumasto; Binti Yunariah; Nurwening Tyas Wisnu; Luthfi Rusyadi (Poltekkes Kemenkes Palu, 2023)
The current disaster management paradigm emphasizes community empowerment, thus enabling the community to become a helping subject, not an object that needs help. Data shows that Indonesia is a country prone to all sources of natural disasters. The purpose of this research is to compile modules in creating a disaster resilient campus. After the modules are compiled, the next step is to socialize the modules, conduct training of trainers, training and evaluate the training that has been carried out based on the modules that have been prepared. Research methods. Quantitative research design, with a descriptive approach. Aims to identify the potential of higher education institutions in efforts to reduce disaster risk in an effort to develop training modules. The population and sample were FGD (Focus Group Discussion) participants and disaster management experts/experts, and 100 module trial participants.The research variables were obtained from the results of literature studies and FGDs. Furthermore, the identification results are used to develop modules that can be used as Field Rehearsal guides. Modules are obtained in 3 ways: identification, FGD and expert consultation. The variables of this study are the presence of disaster courses, the presence of disaster course lecturers, the competence of lecturer training, the existence of training modules for lecturers, the diversity of potential disaster sources. Result.The results of the analysis test on all variables which are learning activities, are valid and reliable. From the results of the analysis, it can be obtained that the item score with a total score is then compared with the r table value (5% significance with a 2-sided test and n = 110) in the amount of 0.195. The decision was that all the r values from the analysis were more than (>) the r table values. Conclusion. The results showed that the modules that had been developed by conducting literature studies, FGDs and expert consuls had been tried out. The results of the analysis test show that the module can be used for disaster risk reduction (DRR) training for campuses. The importance of conducting training by paying attention to the 10 learning activities as disaster training competency standards.